Medicinal uses of honey: a review on its benefits to human health - Rana, Seema; Mishra, Meerambika; Yadav, Dhananjay; Subramani, Senthil Kumar; Katare, Charu; Prasad, GBKS (Progress in Nutrition, 2018)
Honey often referred to as ‘the drink of the gods’, is naturally sweet and a substantially rich source of carbohydrates, amino acids and antioxidants. In spite of being rich in carbohydrates, honey has a low glycemic index and therefore effectively used as a dietary compliance by diabetics. The fructose content of honey has hepatoprotective capability, while the antioxidants present in it provide effective protection against oxidative damage. The therapeutic attribute of honey makes it the food of choice even in infants and diabetics. Honey is endowed with antioxidant, immune modulating, and wound healing, anti-inflammatory, therapeutic, nutritional, antimicrobial and antidiabetic qualities. The present review aims at discussing these capabilities of honey with special reference to its antidiabetic benefits under one dome.